A Phenomenological Study: Forms, Causes, And Coping Strategies of Music Performance Anxiety Among Pianists - Beratio, Nerilyn; Bugtai, Mariella; Enerio, Naryle; Su, Yuhe; Bissil, Brainy; Mendoza, Khristine (12th International Scholars Conference 2025, 2026)
This research study investigates the forms, causes, and coping strategies employed by pianists dealing with music performance anxiety, considering factors such as the demanding nature of performances, the scrutiny of audiences, and the cultivation of a constructive mindset. articulate their experience of anxiety during piano performances, identifies perceived causes of music performance anxiety, and sheds light on the coping mechanisms employed by these musicians. This phenomenological study is anchored in Yerkes-Dodson Law by Yerkes and Dodson (1908), the study involves ten purposely selected participants and employs a phenomenological framework. Data collection involves semi-structured interviews, with subsequent verbatim transcription and translation, followed by thematic analysis. The results illuminate that participants encounter anxiety on cognitive, physical, and behavioral levels, stemming from factors such as inadequate preparation, self-imposed expectations, societal pressure, performance environments, and the complexity of the music performed. Furthermore, participants employ a range of coping strategies, including self-preparation, building self-esteem, seeking social affirmation, musical preparation and focus, self-motivation, and seeking spiritual assurance. These findings contribute valuable insights into the multifaceted nature of music performance anxiety and provide a foundation for developing targeted interventions and support mechanisms for musicians facing such challenges. This research emphasizes the importance of addressing performance anxiety in different facets of the musical domain. For piano students, understanding and confronting the roots of anxiety are essential for effective preparation and personalized coping mechanisms